Culture connection : how developing a winning culture will give your organization a competitive advantage - Parker, Marty (McGraw-Hill, 2012)
The business world is only now beginning to open its eyes to the fact that a powerful corporate culture can generate hard-currency results. But Marty Parker has known this for years. Since 2003, his executive search and cultural assessment firm, Waterstone Human Capital, has focused its recruiting strategy on employee fit and on the best corporate cultures. Each year, the firm's "Canada's 10 Most Admired Corporate Cultures" program singles out companies whose cultures have led to measurable growth, increased profits, and a distinct competitive advantage. Now, Parker reveals the best practices of some of the world's top companies to help you generate extraordinary business results by spearheading cultural change in your own organization. Culture Connection helps you define your vision and gives you invaluable guidance on how to: Set the stage for improved communication, innovation, and performance Provide significant shareholder return Measure and align your organization's efforts Recruit and retain the best people in your industry Culture Connection is filled with advice from top business leaders, including Clive Beddoe, founding shareholder and chairman, WestJet; Isadore Sharp, founder and chairman, Four Seasons Hotels and Resorts; Darren Entwistle, president and CEO, TELUS Corporation; Marc Tellier, president and CEO, Yellow Pages Group; and Michael McCain, president and CEO, Maple Leaf Foods. These leaders know what they're talking about: each represents an organization that has been a previous winner of "Canada's 10 Most Admired Corporate Cultures", and whose performance has outperformed their peers. In fact, the 2010 winners of Canada's 10 outpaced the S & P/TSX 60 by an average of 600 percent. Culture isn't just connected to performance; it drives performance. Today's top companies invest in their corporate cultures, and they don't pull back when times get tough. Even in the most challenging times, they behave like great companies. And that's what they remain. Learn their hard-earned lessons with Culture Connection-and establish the kind of culture that seizes and holds the competitive edge.